The response of inflation to budgetary shocks in Russia: An (S)VAR approach in economically uncertain times - Feriel Dermechi; Ahmed Zakane (The Central European Review of Economics and Management (CEREM), 2024)
Aim: The motivation for this research stems from Russia's notable high levels of government expenditure due to its continual involvement in armed conflicts, which often result in budgetary imbalances and economic policy uncertainty. These factors impact the inflation rate. This study delves into the complex relationship between budgetary shocks, economic uncertainty, and inflation within the context of the Russian economy. The aim of this study is to unravel how budgetary decisions, made amidst a globally uncertain economic environment, influence inflation dynamics. In other words, the objective of this study is to analyse the effects of budgetary shocks on the inflation rate in Russia, taking into account the uncertain context of her economic policy. Design / Research methods: To achieve the objective, we employ a Structural Vector AutoRegression (S)VAR approach, covering the period from 2003-Q1 to 2022-Q4. This methodological approach allows for a comprehensive analysis of how economic uncertainty influences the identification of budgetary shocks within an (S)VAR model. Conclusions / findings: The findings underscore that incorporating the economic uncertainty index into the model yields statistically significant estimates, suggesting that variations in economic uncertainty shape the relationship between budgetary shocks and inflation. This sheds light on the intricate mechanisms through which economic uncertainty influences the behaviours of economic agents and policy decisions, thereby affecting the transmission of budgetary shocks to inflation. In contrast, without the economic uncertainty index, the response of the inflation rate to budgetary shocks is insignificant. Originality / value of the article: This study makes an original contribution by incorporating the Economic Uncertainty Index to better capture budgetary shocks. By showing how uncertainty affects the effectiveness of fiscal policies on inflation, it offers new perspectives on macroeconomic stability. This approach provides a more detailed analysis of the responses of economic actors and their implications for policymakers in volatile economic environments.
Keywords: E31; E62; C51; 330; Russia; economic policy uncertainty; inflation; budgetary shocks; (S)VAR